Loan guarantee schemes in the UK: the natural experiment of the enterprise finance guarantee and the 5 year rule. Issue 20 (27th April 2018) - Cowling, Marc; Robson, Paul; Stone, Ian; Allinson, Gordon
ABSTRACT: Loan guarantee schemes have existed since 1953 (in the US) and are widely used throughout the world to provide financial support to smaller firms by guaranteeing loans from commercial banks. The UK government has been an active supporter of loan guarantees since 1981, and has a long track record of modifying its scheme to reflect changing market conditions and the financing needs of its SME sector. Arguably the two most significant changes occurred in 2008 when the 5-Year Rule on eligibility was removed and in 2009 when the long-standing Small Firms Loan Guarantee Scheme was replaced by the Enterprise Finance Guarantee Scheme. We treat the removal of the 5-Year Rule as a natural policy experiment and empirically question whether, on economic grounds, this was a sensible policy. Our findings suggest that the 5-Year Rule was a better policy choice with regard to employment but had no impact on sales growth.